The ageing athlete: screening prior to vigorous exertion in asymptomatic adults without known cardiovascular disease. Issue 9 (4th September 2009) - Freeman, J; Froelicher, V; Ashley, E
Abstract : The exercise electrocardiogram (ECG) is widely considered the best available test for screening asymptomatic adults without known cardiovascular (CV) disease prior to initiating a vigorous exercise programme due to its prognostic value, widespread availability and low cost. Observational studies have demonstrated an increased relative risk of CV events with positive screening exercise ECG tests in men with diabetes, advanced age, or multiple cardiac risk factors. Recent observational studies have not demonstrated similar prognostic value for exercise ECG testing in asymptomatic healthy women. Despite the predictive ability of exercise ECG testing in several groups, there have been no studies demonstrating a significant impact of screening on morbidity and mortality in completely asymptomatic patients, leading to significant discordance in consensus guidelines on screening. One prospective observational study is ongoing in Italy that may for the first time demonstrate the ability to decrease incident CV events using preparticipation screening exercise ECG testing in adult athletes with targeted exclusion from athletics. Until more conclusive data is available the authors currently recommend screening exercise ECG testing in asymptomatic men with diabetes and asymptomatic men over age 45 with two or more CV risk factors prior to initiating a vigorous exercise programme. Consideration should also be given to screening asymptomatic patients younger than 45 with particularly strong risk factor exposure or elderly patients with fewer than two risk factors.